The implementation of prognostic index and risk grouping in surgically treated cervical carcinoma patients: A prospective validation study - Basheska, Neli; Veljanoska-Petreska, Slavica (Македонско лекарско друштво = Macedonian medical association, 2013)
Introduction. The objective of this prospective study was to validate the prognostic criteria defined by the results of our previous study in an independent population of surgically treated cervical carcinoma patients. Methods. The study group consisted of 340 patients who underwent abdominal hysterectomy with pelvic lymphadenectomy as primary therapy. Based on the scores of the variables (blood vessel invasion, lymph node metastases, tumor diameter, degree of inflammatory reaction at the invasive front, and minimum thickness of uninvolved cervical stroma/parametrial extension) and calculated prognostic index (PI) values, the patients were divided into three prognostic groups. Results. The 5-year disease-free survival (DFS) rates of the low, intermediate, and high-risk groups were 98,82%, 84,57%, and 74,01%, respectively. The differences in DFS rates were statistically significant (P<0,00001). In order to validate the model from our previous study, we have compared DFS rates between the groups. There was no difference in DFS rate between low-risk groups, although the majority of the patients in this study were not irradiated, while radiotherapy was administrated invariably to all the original study patients. Similarly, DFS did not differ significantly between the intermediate-risk groups, which could be expected since radiotherapy was administrated to majority of the patients in this study. In contrast, the high-risk group patients in this study had significantly higher DFS rate (74,01% vs. 44,24%, P=0,0010), probably as the result of the adjuvant chemotherapy administrated to 69% of them. Conclusions. PI could be a sound and reliable basis for appropriate planning of the following therapeutical strategy of the surgically treated cervical carcinoma patients.
Примена на прогностичкиот индекс и поделбата во ризични групи кај хируршки третирани пациенти со карцином на грлото на матката: Проспективна валидациона студија
Keywords: cervical cancer; prognostic factors; disease-free survival; prognostic index; prognostic groups